The Own Education: Between Catholic Legacies and Ethnical Demands - María Isabel González Terreros (Pedagogía y Saberes, 2013)
This paper points a proposal of own education which is implemented in the department of Cauca, in Colombia, which was born from the intention of strengthening the Indian movement and recuperating its culture, which is submerged in a traditional, confessional model of education. These conflicting perspectives –ethnical/confessional- in the mere way they are analyzed in the study, are part of a social-cultural conflict that underlies own education, in which also merge different sectors, stories, legacies and proposals.